REGULARITAS DAN RELASI GREEN PADA SEMIGRUP TRANSFORMASI LINEAR PARSIAL INJEKTIF DENGAN RESTRIKSI RANGE - Ade Ima Afifa Himayati (Jurnal Karya Pendidikan Matematika, 2020)
Injective partial linear transformations in the vector space V and the function composition operations form semigroups called semigroups of injective partial linear transformations denoted by I (V). Suppose Z is a subspace in a vector space V, then the set of all members of I (V) whose function results are contained in Z to the function composition operation is also a semigroup denoted by I (V, Z) which is called a semigroup of injectable partial linear transformations with range restrictions. . In this article, we will examine how the characteristics of regular elements and the characteristics of two set members in I (V, Z) are related to Green using the literature study method. The results of the research in this article are the necessary and sufficient conditions needed so that any element is called a regular element and the characteristics of the two members of the set I (V, Z) are related.